IDENTIFIKASI GAYA BELAJAR VAK MELALUI EDUKASI PARENTING DI SD ASSUNNIYAH KENCONG JEMBER - Akhmad Rudi Masrukhin; M. Nafiur Rofiq; Defri Khoirul Rizki (Universitas Al-Falah As-Sunniyah Kencong Jember, 2026)
Abstract. This community service program aimed to identify the distribution of Visual, Auditory, and Kinesthetic (VAK) learning styles among prospective first-grade students and to enhance parental understanding through school–family partnership-based parenting education. A participatory community-based approach with a descriptive-educational intervention design was employed. Data were collected through structured questionnaires and observations involving 30 prospective students, followed by an interactive parenting session. The findings revealed that 40% of students demonstrated a visual learning tendency, while auditory and kinesthetic preferences each accounted for 30%. These results highlight the importance of implementing multisensory instructional strategies in early primary education. Furthermore, 83% of parents demonstrated improved understanding of their children’s learning characteristics, and 78% expressed readiness to apply supportive learning strategies at home. The program confirms that integrating learning style identification with parenting education effectively strengthens school–family collaboration in supporting school readiness. Future initiatives should include longitudinal monitoring to assess long-term impacts on student adaptation and academic achievement.